English Language Teaching through Virtual Classroom during COVID-19 Lockdown in Bangladesh: Challenges and Propositions - Md. Mozaffor Hossain (Journal of English Education and Teaching, 2021)
Bangladesh, like many other countries of the world, has been strongly hit by COVID-19 pandemic and her education sector, among other essential fields of life, is under strict lockdown. The onsite mode of institutional education is absolutely stopped although of late educational institutes mostly non-governmental ones, with the permission as well as guidelines of the Ministry of Education and/or University Grand Commission (UGC), have adopted and are implementing online classes as an alternative way of imparting education. Accordingly, English language teaching and learning is happening in full swing via online classes. However, many have raised questions as to the rationale of executing virtual education and assessment, especially how to teach and assess the four skills, i.e. Listening, Reading, Writing and Speaking, of English language through online sessions when majority of the teachers and students are fundamentally bereft of the essential technological resources and internet coverage. On these notes, the current study has sought to learn the experience and perceptions of 50 teachers and 50 students who are currently teaching and learning English through online classes at various institutes across the country. The researcher has interviewed the sample population with two disparate open-ended questionnaires through e-mail and social networking cites, like Messenger and Facebook to learn teachers’ and learners’ experiences and suggestions on the present online education nationwide and how much feasible it is if COVID-19-pandemic lockdown persists longer only to make education system run through a “new normal” manner. The study offers crucial findings relating to a number of technology and internet-related unsolved issues. Simultaneously, it suggests ineludible modifications to be accomplished on teachers, learners, educational institutions, technological resources and internet communications if ELT through online is to be made fruitful.